Unanticipated difficult airway in a neonate: no child's play. - S. Podder; S. Raghavan Nandyal; S. Sinha; S. Raghavan Nandyal; A. Kumar HD (Pediatric Anesthesia and Critical Care Journal, 2022)
Neonatal intubations can be challenging despite unre- markable external findings and optimal laryngoscopic views. A 4-day-old, pre-term, was scheduled for an ex- ploratory laparotomy. Our first attempt at intubation with a Miller's blade was unsuccessful. After two unsuccess- ful attempts, a senior anesthesiologist was called for help. Mask ventilation was resumed between all the attempts. Hemodynamic instability was identified and treated. Fi- beroptic bronchoscopy revealed a laryngeal anomaly, and further attempts were deferred. Spontaneous respiratory efforts returned, and the surgery was rescheduled. The neonate developed respiratory distress that evening. An emergency tracheostomy was deemed necessary and a tracheostomy tube was placed. With a surgical airway in place, we proceeded with exploratory laparotomy. The child was stable throughout the surgery. Neonates may present with unpredictably demanding air- ways. The absence of requisite societal guidelines on the management of difficult neonatal airways makes the management challenging.